Efektivitas Program Pemberdayaan Petani Berbasis Partisipasi Masyarakat di Desa Torok Golo, Kecamatan Rana Mese Manggarai Timur - Matias Muhi Ledjab; Sri Kamariyah; Nihayatus Sholicah; Dandy Patrija W (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Torok Golo Village in Rana Mese District, East Manggarai, is an agrarian area with significant agricultural potential but faces various structural challenges, such as limited access to agricultural technology, weak farmer institutions, and low community participation in village development planning processes. This study aims to evaluate the effectiveness of a community-based farmer empowerment program in the area. A qualitative approach was used with a descriptive-qualitative research design. Data were collected through in-depth interviews, participatory observation, and documentation involving local actors, including farmers, extension workers, village officials, and program facilitators. Data analysis followed the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results show that the empowerment program has enhanced farmers' capacities in production and group collaboration, and there has been active community participation during the implementation phase. However, participation in the planning and evaluation stages remains suboptimal, and the institutional structure of farmer groups still requires strengthening. Other weaknesses include limited market access and low utilization of modern agricultural technologies. The study concludes that program effectiveness heavily depends on sustained community participation across all stages and structural support from the government and assisting institutions. Future research is recommended to explore technology-based empowerment models combined with the strengthening of local institutions to better adapt to the needs of rural communities in remote areas.